Community participation in the development of ward-based secondary schools in Tanzania - Anania, Ahadi M. (2019)
Community participation is widely advocated to enhance development. In Tanzania, it is embraced as a strategy to support the government in service provision and development. It is also regarded as a way to inspire community commitment, ownership, and hence sustainability. Community participation (CP) is a dominant strategy in the development of Ward-Based Secondary Schools (WBSS) in Tanzania. However, the schools remain constrained by inadequate facilities and infrastructure. This study set out to explore CP in the development of WBSS in the current education policy context of Tanzania. It explored the nature and extent of community members’ involvement in the development of WBSS, and the extent to which they participate in funding the schools’ development. The study further aimed to explore perceptions of community members about their participation and the factors that facilitate and hinder their participation in the development of WBSS. The study adopted a constructivist paradigm, employing a multiple case study design to generate thick and holistic data from four WBSS, selected purposively. Nine participants were drawn from each case school and its community through stratified and purposive sampling to examine participation of CMs in the development of WBSS. Interviews, observations and documentary reviews were the methods employed in data collection. Thematic analysis was used to develop themes inductively from data, linked to the research questions. The study found that CMs were involved through contributing their views during meetings and making monetary contributions for school development. However, the study also established that CMs were not genuinely involved in planning and decision-making, thus limiting their motivation to participate. The findings show that there was generally a low level of CP, attributed to the low income of community members, limited approaches for involving CMs, policy contradictions, and the politics of multi-partyism. These barriers partly result in CMs’ perception that it is the responsibility of the government to manage and finance the development of WBSS. Such factors constitute major barriers to genuine CP, making it difficult for WBSS to develop despite the shared responsibility of several stakeholders, including the government and communities. The findings lead to a grounded-theory model for genuine community participation. The study provides recommendations to policy makers at the national level, for practice at local government level, and for further research. It recommends that, policies should respond to the realities of CMs’ lives, with respect to participation and development. They should be clear and well disseminated to avoid misinterpretations engendered by local and national politics. The government’s ability to support schools should be made clear to CMs, and there should be clear delineation of responsibilities among stakeholders. Finally, the study recommends further research to involve other categories of schools, and widening the geographical coverage of the study, as well as exploring the perspectives of government officials on community participation, as this remains an important strategy for school development.